Is Dosing of Therapeutic Immunoglobulins Optimal? A Review of a Three-Decade Long Debate in Europe - Kerr, Jacqueline; Quinti, Isabella; Eibl, Martha; Chapel, Helen; Späth, Peter J.; Sewell, W. A. Carrock; Salama, Abdulgabar; van Schaik, Ivo N.; Kuijpers, Taco W.; Peter, Hans-Hartmut (Frontiers in Immunology, 2014)
The consumption of immunoglobulins (Ig) is increasing due to better recognition of antibody deficiencies, an aging population and new indications. This review aims to examine the various dosing regimens and research developments in the established and in some of the relevant off-label indications in Europe. The background to the current regulatory settings in Europe is provided as a backdrop for the latest developments in primary and secondary immunodeficiencies and in immunomodulatory indications. In these heterogeneous areas, clinical trials encompassing different routes of administration, varying intervals and infusion rates are paving the way towards more individualized therapy regimens. In primary antibody deficiencies adjustments in dosing and intervals will depend on the clinical presentation, effective IgG trough levels and IgG metabolism. Ideally, individual pharmacokinetic profiles in conjunction with the clinical phenotype could lead to highly tailored treatment. In practice, incremental dosage increases are necessary to titrate the optimal dose for more severely ill patients. Higher intravenous doses in these patients also have beneficial immunomodulatory effects beyond mere IgG replacement. Better understanding of the pharmacokinetics of Ig therapy is leading to a move away from simplistic ‘per kg’ dosing. Defective antibody production is common in many secondary immunodeficiencies irrespective of whether the causative factor was lymphoid malignancies (established indications), certain autoimmune disorders, immunosuppressive agents or biologics. This antibody failure, as shown by test immunisation, may be amenable to treatment with replacement Ig therapy. In certain immunomodulatory settings (e.g. ITP) selection of patients for Ig therapy may be enhanced by relevant biomarkers in order to exclude non-responders and thus obtain higher response rates. In this review the developments in dosing of therapeutic immunoglobulins have been limited to high and